Pengaruh Kombinasi Pestisida Nabati Terhadap Intensitas Serangan Serangga Hama Pada Tanaman Tomat (Solanum lycopersicum L.) - Nurwana Nurwana; Sonja V.T. Lumowa; Herliani Herliani; Sri Purwati (Institut Agama Islam Negeri Kerinci, 2024)
The Effect of Combination of White Ginger (Zingiber officinale var Amarum) and Bay Leaf (Syzygium polyantum) Botanical Pesticides on the Intensity of Insect Pest Attacks on Tomato Plants (Solanum lycopersicum L.). This study aims to determine the effect of the combination and to determine the most effective concentration for reducing insect pest attacks on tomato plants (Solanum lycopersicum). The type of research used is an experiment using a randomized block design (RAK) consisting of 5 treatments, namely, T0 (Control), T1 (15%), T2 (30%), T3 (45%), and T4 (60%) with 5 repetitions. Then analyzed using 1-way Anova. Based on the results of the calculation of 28 HST, where Fcount (123.28) > (4.77), at 42 HST Fcount (93.66) > (4.77), at 56 HST Fcount (59.52) > (4.77), at 70 HST Fcount (30.85) > (4.77), and at 84 HST Fcount (33.93) > (4.77). So the most effective concentration in suppressing insect pests is the concentration of T4 (60%). Based on data analysis, there is a very real effect of administering the plant pesticides White Ginger (Zingiber officinale var Amarum) and Bay Leaves (Syzygium polyantum) on the intensity of insect pest attacks on tomato plants (Solanum lycopersicum L.).